Symposium 6: Accessible Technology for Networked Learning - Jesshope, Chris; Zhang, Zhenzi; Gehne, Regina; Heinrich, Eva; Loomes, Maureen; Shafarenko, Alex; Loomes, Martin (Proceedings of the International Conference on Networked Learning, 2002)
This paper will describe the TILE MLE, which comprises a learning content management system and an educational delivery system; it will focus on the former as the delivery framework has been described elsewhere. From a pedagogical point of view, content creation and delivery are the two key factors in web-based learning systems. When supported by the Internet, content delivery are relatively cheap. But creating high quality online learning content is very expensive. Currently different organizations are creating similar content for their own need, with little reuse of content. This is a waste of valuable resources and is the reason why there is an imperative need for standards-compliant content management systems to facilitate content development and deployment. E-learning content management systems face the challenge of collecting, organizing, managing, maintaining, re-using, delivering and targeting the content. We must differentiate between a content-management system and authoring tools for content creation. The latter are used to create content that is organised into a course. This may be animations, graphics, text, audio, video or other multimedia segments. These learning objects are organised and catalogued by the learning content management system and this creates units of study or on-line courses that can be navigated and perhaps monitored. That unit of study usually has structure, which may include hierarchy and precedence. An LCMS should support the management of any content level, which includes multimedia segments, learning objects or units of study. The design of such a system is described her, together with an analysis of the issues considered. Papers: A Content Management System for the TILE Managed Learning Environment Chris Jesshope and Zhenzi Zhang Interactive Multimedia for Dummies Regina Gehne and Chris Jesshope Beyond Just Replay: Multimedia Support for Online Learning Eva Heinrich Teaching Mathematics with Audiograph Maureen Loomes, Alex Shafarenko and Martin Loomes CHALLENGE - An intuitive, goal-based scenario authoring system for electronic learning Terry Stewart and Paul Bartrum